Delinquency Risk as a Function of Number of Early Onset Problem Behaviors - Mason, Alex W. (International journal of offender therapy and comparative criminology, 2001)
This study examined delinquency risk as a function of number of early onset problem behaviors retrospectively self-reported by a sample of middle-adolescent boys and girls. Number of early first experiences of problem behaviors was linearly associated with increased frequency of delinquency among the predominantly White and middle-class high school students. In addition, number of early onset behaviors explained a small, but significant, amount of variance in self-reported frequency of delinquency over and above that explained by prior delinquency and additional psychosocial variables (e.g., peer deviance, family support). Finally, results demonstrated that the magnitude of risk for incarceration during adolescence increased in proportion to the number of early first experiences of problem behaviors. These findings are interpreted in light of the extant literature, and implications for the development of preventive interventions are discussed